Pengaruh Penerapan Akuntansi Forensik dan Kemampuan Auditor Investigatif dalam Pengungkapan Penipuan dengan Profesionalisme sebagai Moderator pada Badan Pemeriksa Keuangan Perwakilan Provinsi Riau - Ria Febriana; Amir Hasan; Andreas Andreas (Jurnal Ekonomi, 2019)
This study aims to analyze the effect of the implementation of forensic accounting and the ability of investigative auditors to disclose fraud related to auditor professionalism. This research was conducted at the office of the Badan Pemeriksa Keuangan (BPK) RI representative of Riau Province. The sampling technique used in this study was a total sampling. Analysis of data using WarpPls 5.0 2018 software. The results of the study show that : 1) implementation of forensic accounting to significantly influence on fraud disclosure, 2) ability of investigative auditors to significantly influence on fraud disclosure, 3) professionalism doesn’t moderate the relationship between the implementation of forensic accounting and disclosure of fraud, 4) professionalism moderated the relationship of investigative auditor’s ability and fraud disclosure.